Zero Food Waste: Ekoenzim Sebagai Upaya Pembentukan Karakter Peduli Lingkungan Di SDN 1 Munjuljaya - Hisny Fajrussalam; Nenden Permas Hikmatunisa; Alida Zia Fatimah; Anti Oktaviani; Khairun Nabilah; Khomsanuha Amanaturrizqi; Oryza Sativa; Riska Zulfa Luthfiyyah (CV. Multi Kreasi Media, 2024)
One of the characteristics of a healthy environment is an environment that is free of waste. Waste itself can be defined as the remaining waste of products that have been processed or consumed and are no longer used. This problem can be sustainable if not handled wisely because it can lead to water and air pollution, an increase in greenhouse gases, and the spread of disease. As an effort to deal with waste, especially household waste, students carry out community service as a form of output from the implementation of the Educational Professional Strengthening Program (P3K) which is carried out at SDN 1 Munjuljaya with the target of all school residents and student guardians by implementing the Zero Food Waste program through ecoenzyme products. This service aims to invite the school community to utilize the remaining household waste to make ecoenzyme products to improve the character of environmental care at SDN 1 Munjuljaya. The method used in this activity is socialization with a persuasive approach to educating students and parents to be more concerned about the utilization of organic waste by utilizing ecoenzyme to form the character of environmental care at SDN 1 Munjuljaya.